Pengaruh Bimbingan Kelompok Melalui Media Audio Visual Terhadap Motivasi Belajar Siswa - Taufik Agung Pranowo; Amalia Prihastanti (ILIN Institute Makassar, 2020)
The study aims: 1) to determine the conditions of vocational students 'learning motivation, 2) determine the effect of group guidance services through audio visual media on the motivation of vocational students' learning. This type of research is an experiment with one group pre-test and post-test design models. The population was 102 students and the sample of this study was 10th grade students of SMK N 1 Pejawaran with 10 students. Data analysis using the Wilcoxon test. The results of this study 1) the learning motivation of students of class X SMK N 1 Pejawaran Academic Year 2018/2019 is still low, based on the distribution of students' learning motivation scale with a low category of 33 students (32.4%), in the medium category of 69 students (67, 6%), 2) Group Guidance service using audio visual media has an effect in increasing student motivation in class X SMK N 1 of Academic Year 2018/2019, with a sig. = 0.008 <0.05. The conclusions in this study are 1) Class X students learning motivation SMK N 1 Pejawaran still moderate, and 2) group guidance services using audio visual media influence the learning motivation of class X students of SMK N 1 Pejawaran.